1978
DOI: 10.1002/jcu.1870060404
|View full text |Cite
|
Sign up to set email alerts
|

Gray scale B scan characteristics of intra‐abdominal cystic masses

Abstract: A comparison of the gray scale characteristics of 119 intra-abdominal cystic masses was performed. Each cystic mass was evaluated with regard to: 1) The presence or absence of internal echoes, septa, and fluid-fluid levels; 2) The appearance of the wall; 3) Conformity to adjacent organs and, 4) Changes in the surrounding soft tissues. Abscesses, hematomas, lymphoceles, urinomas, and necrotic tumors were evaluated. Necrotic tumors and some abscesses and hematomas have specific sonographic characteristics. In mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Although the presence of some dependent echoes in these lesions is often seen, it is less common to see a definite fluid-fluid level. In the study by Hill and Sanders involving 119 intraabdominal cystic masses, they found well-defined , fluid-fluid levels only in abscesses and hematomas (2).…”
Section: Discussionmentioning
confidence: 98%
“…Although the presence of some dependent echoes in these lesions is often seen, it is less common to see a definite fluid-fluid level. In the study by Hill and Sanders involving 119 intraabdominal cystic masses, they found well-defined , fluid-fluid levels only in abscesses and hematomas (2).…”
Section: Discussionmentioning
confidence: 98%
“…As mentioned before, partly for this reason the 2.4‐mm objects were excluded in the present study. Furthermore, a study investigating the characteristics of intra‐abdominal cystic masses showed that a variation in the number of internal echoes could be found in all the cystic masses examined (21) . It is therefore an advantage to include a range of contrast levels when studying the ability of a system to reproduce low‐contrast details.…”
Section: Discussionmentioning
confidence: 99%
“…In case 1, the evenly and diffusely distributed fine echoes probably represented debris from chronic infection or inflammation [4]; Echo-free spaces caused by pus occupied most of the mass in case 2; The high internal irregular echoes of the gauze were clearly shown in both cases [5]. Abscess, hematoma, and pancreatic pseudocysts may have similar ultrasonic appearance [6], but high internal irregular echoes are highly specific for retained gauzes.…”
Section: Discussionmentioning
confidence: 99%